Ultrafast Laser Processing of Diamond Materials: A Review - Apostolova, Tzveta; Kurylo, Vasyl; Gnilitskyi, Iaroslav (Frontiers in Physics, 2021)
Diamond laser engineering is of great importance for designing devices, which find applications in radiation sensing and quantum technologies. A review of the present state of the art of experimental and theoretical studies on ultrashort laser irradiation of diamond is presented. For a wide range of laser parameters, the optimization of laser-induced electronic, optical and structural modifications of diamond requires quantitative understanding of the microscopic processes underlying the high electronic excitation in the material.